Evaluating Mandatory Tahfȋẓ Quran Program Implementation at Madrasah - Siti Muawanah; Abdun Said; Ridwan Furqoni; Umi Muzayanah; Mustolehudin Mustolehudin (Jurnal Pendidikan Islam, 2022)
Mandatory tahfȋẓ is a program initiated by the Regional Office of the Ministry of Religion Affairs Yogyakarta Province. The core of the program is that every madrasah is required to target its students to memorize the Quran at least one juz before graduating from studying at the madrasa. This paper describes and evaluates the mandatory tahfȋẓ program at Madrasah Tsanawiyah in Yogyakarta which has been running since 2016. The approach used is quantitative-qualitative. Data were collected using observation techniques, interviews, and questionnaires. The results of the study show that through the CIPP evaluation model (context, input, process, and product) the mandatory tahfȋẓ program at Madrasah Tsanawiyah in Yogyakarta is running well. In terms of the context evaluation, 5% of madrasas include tahfiz in their vision and mission. The program does not have full parental support. When it comes to input aspect, the mandatory tahfȋẓ activities are carried out by 67% of teachers with bachelor's degrees. For evaluation process, madatory tahfȋẓ is carried out for 2-8 hours of lessons. The effectiveness of madtory tahfȋẓ evaluation products is below 30%.